On the tidal formation of dark matter-deficient galaxies. Issue 2 (16th December 2021) - Ogiya, Go; van den Bosch, Frank C; Burkert, Andreas
ABSTRACT: Previous studies have shown that dark matter-deficient galaxies (DMDG) such as NGC 1052-DF2 (hereafter DF2) can result from tidal stripping. An important question, though, is whether such a stripping scenario can explain DF2's large specific frequency of globular clusters (GCs). After all, tidal stripping and shocking preferentially remove matter from the outskirts. We examine this using idealized, high-resolution simulations of a regular dark matter-dominated galaxy that is accreted on to a massive halo. As long as the initial (pre-infall) dark matter halo of the satellite is cored, which is consistent with predictions of cosmological, hydrodynamical simulations, the tidal remnant can be made to resemble DF2 in all its properties, including its GC population. The required orbit has a pericentre at the 8.3 percentile of the distribution for subhaloes at infall, and thus is not particularly extreme. On this orbit the satellite loses 98.5 (30) per cent of its original dark matter (stellar) mass, and thus evolves into a DMDG. The fraction of GCs that is stripped off depends on the initial radial distribution. If, at infall, the median projected radius of the GC population is roughly two times that of the stars, consistent with observations of isolated galaxies, only ∼20 per cent of the GCs are stripped off. This is less than for the stars, which is due to dynamical friction counteracting the tidal stirring. We predict that, if indeed DF2 was crafted by strong tides, its stellar outskirts should have a very shallow metallicity gradient.